Motivating frontline employees: Role of job characteristics in work and life satisfaction. (June 2016) - Zhao, Xinyuan (Roy); Ghiselli, Richard; Law, Rob; Ma, Jing
Abstract: This study examined the intrinsic motivation for hospitality jobs and the effects of job characteristics on job satisfaction, job stress, and life satisfaction. Data were obtained from the survey responses of 401 frontline employees working at six full-service, upscale hotels in China. Results indicated that autonomy, task identity, and task significance reduced job stress, feedback increased job satisfaction, and task significance enhanced life satisfaction. Surprisingly, skill variety was negatively associated with job satisfaction, but positively associated with job stress. The composite Motivating Potential Score was positively associated with job satisfaction, but negatively associated with job stress. One recommendation is for hospitality organizations to analyze their service jobs to improve the intrinsic motivation of their employees.